2017
DOI: 10.3892/ol.2017.7420
|View full text |Cite
|
Sign up to set email alerts
|

CITED2 attenuates macrophage recruitment concordant with the downregulation of CCL20 in breast cancer cells

Abstract: The transcriptional co-regulator Cbp/p300-interacting transactivator with Glu/Asp-rich carboxy-terminal domain-2 (CITED2) may promote breast tumor growth; however, the mechanisms by which its effects are mediated remain to be fully elucidated. Tumor-associated macrophages serve an important function in tumor development and progression and are recruited by chemotactic factors produced by cells within the tumor microenvironment. The present study assessed the effects of CITED2 silencing on macrophage recruitmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 34 publications
0
16
0
Order By: Relevance
“…Interestingly, IRGM also promotes MIP‐3α release and inhibited IL‐6 release (Figure D and 4E). The chemokine MIP‐3α has not reported a role in M2 macrophage polarization, while MIP‐3α could influence tumor growth by inducing macrophage recruitment as a chemokine (Jayaraman et al, ), which suggested IRGM could recruit macrophage into glioma by releasing MIP‐3α. We speculate both IL‐8 and MIP‐3α play key roles in glioma immune suppressive microenvironment formation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, IRGM also promotes MIP‐3α release and inhibited IL‐6 release (Figure D and 4E). The chemokine MIP‐3α has not reported a role in M2 macrophage polarization, while MIP‐3α could influence tumor growth by inducing macrophage recruitment as a chemokine (Jayaraman et al, ), which suggested IRGM could recruit macrophage into glioma by releasing MIP‐3α. We speculate both IL‐8 and MIP‐3α play key roles in glioma immune suppressive microenvironment formation.…”
Section: Discussionmentioning
confidence: 99%
“…IL‐8 promotes a pro‐oncogenic inflammatory microenvironment by inducing M2‐type tumor‐associated macrophages (TAMs) (Xiao et al, ; Li et al, ). The chemokine MIP‐3α (also called CCL20) could influence tumor growth through mediating macrophage recruitment (Jayaraman et al, ). IL‐6 is a multifunctional cytokine released by M1 macrophages as proinflammatory cytokine, and could inhibit M2 macrophages polarization (Sansone et al, ; Chishti et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…For example, it is reported that CCL20, a ligand for CCR6, is abundant in PyMT mammary tumors and genetic deletion of Ccr6 gene in PyMT mice significantly reduces the number of TAMs in mammary tumors ( 68 ). Although the cell type that secretes CCL20 is unknown in the PyMT model, a recent study demonstrates that MDA-MB-231 human breast cancer cells express high level of CCL20 and that inhibition of CCL20 expression in cancer cells reduces TAM accumulation in xenografts ( 69 ). It is also reported that a highly metastatic derivative of MDA-MB-231 cells (named BM1) expresses high levels of CCL5 (a ligand for CCR5) and treatment of BM1 tumor-bearing mice with a CCR5 antagonist significantly reduces the number of TAMs in tumors ( 70 ).…”
Section: Chemokines That Promote Accumulation Of Pro-metastatic Macromentioning
confidence: 99%
“…These results suggest that breast cancer cells can utilize CCL20-CCR6 and CCL5-CCR5 signaling in order to recruit TAMs. In the MDA-MB-231 breast cancer model ( 69 ), expression of CCL20 and TAM accumulation in xenografted tumors are suppressed by knock down of Cbp/p300-interacting transactivator with Glu/Asp-rich carboxy-terminal domain-2 (CITED2), a transcriptional co-regulator whose expression is increased in human invasive ductal carcinoma compared to normal mammary tissues and further enhanced in metastatic breast cancer ( 71 , 72 ). In the BM1 as well as 4T1 mammary tumor models, forced expression of Raf kinase inhibitory protein (RKIP) suppresses CCL5 secretion from cancer cells and reduces TAM accumulation in the xenograft ( 70 , 73 ).…”
Section: Chemokines That Promote Accumulation Of Pro-metastatic Macromentioning
confidence: 99%
“…Alternatively, CITED2 may in this case act as co-activator of other transcription factors, such as SMAD2/3[ 18 ], which are mediators of TGF-β signaling pathway, or TFAP2A, showed to cooperate with CITED2 for normal vascularization of the myocardium during heart development[ 70 ]. Other studies also reported a reduction in primary tumor growth due to the attenuation of tumor-associated macrophage (promoting tumor development and progression) recruitment in response to CITED2 depletion in cancer cells and the consequent downregulation of the macrophage chemoattractant CCL20[ 71 ]. This suggests that CITED2 promotes tumor-associated macrophage recruitment and infiltration in breast tumors.…”
Section: Cited2 and Hypoxia In Cancermentioning
confidence: 99%